2022
DOI: 10.3390/antibiotics11010055
|View full text |Cite
|
Sign up to set email alerts
|

A VetCompass Australia Study of Antimicrobial Use in Dog-to-Dog Bite Wounds (1998–2018)

Abstract: Although dog-to-dog bite wounds (DBW) are a common presentation to veterinary clinics, antimicrobial prescribing habits of Australian clinics have not been reported. This study determined the frequency and results of DBW cultures; antimicrobial selection; and importance class of antimicrobials prescribed relative to wound severity, geographic location, or year. A systematic sample of 72,507 patient records was retrieved from the VetCompass Australia database. Records for 1713 dog bite events involving 1655 dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…AMR bacteria are not necessarily more virulent, however, delays in infection control due to ineffective initial treatment and testing required to determine appropriate therapy, dramatically increases the cost of medical care, and impacts human and animal patients' health [14]. Whilst the AMR implications of antimicrobial use in agriculture, aquaculture, companion animals and equids are established and the subject of considerable quantitative and qualitative research, there is a knowledge gap with respect to antimicrobial use in laboratory animals, particularly research rodents [15][16][17]. This is important to understand, given the considerable number of research rodents used worldwide, estimated to exceed 120 million, and their utility in biomedical research, meaning use has only grown with time [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMR bacteria are not necessarily more virulent, however, delays in infection control due to ineffective initial treatment and testing required to determine appropriate therapy, dramatically increases the cost of medical care, and impacts human and animal patients' health [14]. Whilst the AMR implications of antimicrobial use in agriculture, aquaculture, companion animals and equids are established and the subject of considerable quantitative and qualitative research, there is a knowledge gap with respect to antimicrobial use in laboratory animals, particularly research rodents [15][16][17]. This is important to understand, given the considerable number of research rodents used worldwide, estimated to exceed 120 million, and their utility in biomedical research, meaning use has only grown with time [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the AMR implications of antimicrobial use in agriculture, aquaculture, companion animals and equids are established and the subject of considerable quantitative and qualitative research, there is a knowledge gap with respect to antimicrobial use in laboratory animals, particularly research rodents [15][16][17]. This is important to understand, given the considerable number of research rodents used worldwide, estimated to exceed 120 million, and their utility in biomedical research, meaning use has only grown with time [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…2,5,12,20 However, a recent study demonstrated that C&S of DBW by veterinarians is rarely performed. 21 Currently there is limited published data on the most cultured organisms from DBW in South East Queensland (SEQ). Data reporting antimicrobial susceptibility patterns for bacteria isolated from SEQ DBW will improve first choice antimicrobial selection, thereby reducing the rate of development of antimicrobial resistance, improve treatment success and outcomes.…”
mentioning
confidence: 99%